Recording media configurations for double-layered bit-patterned magnetic recording - Chaiwat Buajong; Chanon Warisarn (My University, 2024)
The current magnetic recording technology is approaching its recording density limit. Recently, concepts focused on vertically stacking multiple recording media have gained momentum, driven by the potential to significantly expand recording density. The key challenge for such a system involves methods capable of efficiently separating data originating from the upper and lower layers within a single readback signal. To address this challenge, we first propose two distinct configurations of recording media in bit-patterned magnetic recording (BPMR) system with double recording layers. In both configurations, the centers of islands on the lower layer are positioned at the gaps between magnetic islands on the upper layer. This achieves the separation of the individual layer signals since the centers of islands in both layers are deliberately misaligned. Moreover, the equalizer design that takes the input data from both layers into consideration is also proposed. Simulation results demonstrate that when employing the same detector, the proposed configurations of the double-layered BPMR systems achieve better performance than the single-layered BPMR system.
Keywords: Patterned media; Area density; SIGNAL (programming language); Cellular Automata and Applications